Madagascar - Post Primary Education : Developing the Workforce, Shaping the Future - Transformation of Madagascar's Post-Basic Education - World Bank (Washington, DC, 2012)
The main purpose of this report is to provide analytical inputs for the development of post-basic education reforms. Specifically, the report identifies and prioritizes: (i) the need for change in the structure, content and delivery of Madagascar's post-basic education and training system, and (ii) the key reforms in financing, governance and sub-sector management required to support changes to the structure, content and delivery of the post-basic system. The Madagascar Action Plan (MAP) outlines an ambitious development strategy, focusing on promoting investment in high growth sectors and regional development. If successful, it will change the demand for skills in fundamental ways. Since 2005, foreign direct investment has increased rapidly. Madagascar's core challenges and the window of opportunity provided by the implementation of basic education reform imply that reform must improve the quality and relevance of post-basic education, while putting cost-effective mechanisms for expanding access in place. Post-basic reform should not focus exclusively on a massive expansion of the existing post-basic system. Instead, successful reform will: (i) focus first on improving educational content (structure, curriculum, teaching, and process) and linkages with the economy; (ii) increase coverage, cost-effectively; and (iii) strengthen the enabling framework for reform (governance, finance, and sub-sector management). Reforms aimed at improving educational content must accomplish three objectives: (i) meet the skilled labor requirements of the economy's key growth sectors, in the short to medium term; (ii) gradually build professional capabilities in the key growth sectors, also in the short to medium term; and (iii) help youth to develop the knowledge, skills and attitudes - employability skills - that will allow them to participate in and adapt to the changing labor market over time.